2010
DOI: 10.3354/cr00869
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and chromosomal inversions in Drosophila subobscura

Abstract: In natural populations, the large changes in chromosomal structure occurring through chromosomal inversions show pronounced variations in frequency that often correspond to temporal and spatial climatic trends, which suggests that they may be employed to monitor the impact of global warming. Here we review and update the evidence on the association between chromosomal inversions and climate in D. subobscura, which provides one of the best studied models in this context. Chromosomal inversion frequencies of D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 97 publications
(82 reference statements)
2
71
0
Order By: Relevance
“…Montane tropical biota are believed to be particularly vulnerable to global warm ing effects (Sheldon et al 2011). Several longterm studies on Drosophila inversion polymorphisms have shown that changes in inversion frequencies can be a valuable tool to monitor rapid genetic shifts caused by climatic change (Stamenkovic-Radak et al 2008, Balanyà et al 2009, Levitan & Etges 2009; for review see: Rieseberg 2008 andRezende et al 2010). None of these studies, however, addresses the potential effects of climate change on a Drosophila Neotropical species.…”
Section: Introductionmentioning
confidence: 99%
“…Montane tropical biota are believed to be particularly vulnerable to global warm ing effects (Sheldon et al 2011). Several longterm studies on Drosophila inversion polymorphisms have shown that changes in inversion frequencies can be a valuable tool to monitor rapid genetic shifts caused by climatic change (Stamenkovic-Radak et al 2008, Balanyà et al 2009, Levitan & Etges 2009; for review see: Rieseberg 2008 andRezende et al 2010). None of these studies, however, addresses the potential effects of climate change on a Drosophila Neotropical species.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, genetically determined variation in traits related to fitness along geographic gradients are thought to be the result of such adaptive evolution (e.g. Hoffmann et al 2002, Castañeda et al 2005, Collinge et al 2006, Rezende et al 2010. Because of the strong covariance between temperature and geographic clines, analyzing clinal variation has become a key element in investigating adaptive (thermal) evolution (Bubliy & Loeschcke 2005, Karl et al 2008a, 2009a, de Jong et al 2010.…”
Section: Dealing With Temperature Variationmentioning
confidence: 99%
“…Its potency as a selection agent is evident by various macro-ecological patterns explained by temperature, such as species distributions (Cossins andBowler 1987, Hoffmann andParsons 1991) or clinal variation within species (Rezende et al 2010). Effects of temperature are observed at all levels of phenotypic organization from molecules to behavior and life history of an organism.…”
mentioning
confidence: 99%